Gender Equality in Muslim-Majority Countries - Moamen Gouda; Niklas Potrafke (Center for Economic Studies and ifo Institute (CESifo), 2016)
Discrimination has been documented against women in Muslim-majority countries. Constitutions differ among Muslim-majority countries. By using women's rights indicators and exploiting cross-country variation, we find that discrimination against women is more pronounced in countries where Islam is the source of legislation. Constitutions changed in only four Muslim-majority countries since 1980. We discuss anecdotal evidence to what extent women's rights changed as a consequence of new constitutions. Empirical studies should thus distinguish between types of Muslim-majority countries.
Keywords: D63; I39; J16; O11; Z12; 330; gender equality; countries with Muslim majority; Al-Azhar's Islamic constitution